2014
DOI: 10.1590/s2179-975x2014000400008
|View full text |Cite
|
Sign up to set email alerts
|

Differential environmental impacts on small and medium size rivers from center of São Paulo State, Brazil, and regional management perspectives

Abstract: AIM: This study aimed to evaluate, comparatively, the influence of distinct environmental impacts in the watershed on the rivers Capivara, Lavapés, Araquá and Pardo and the transference of effects downstream. METHODS: The limnological/water quality study was carried out in rainy (March/2007) and dry (September/2007) seasons, considering 17 sampling stations. RESULTS: Variables such as channel width and depth, water velocity and temperature increased towards the river's mouth; water transparency, velocity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…All twelve stations in this study showed high conductivity values. Sediment ingress because of the lack of riverside vegetation at all stations could be an explanation for these high values (Reis-Oliveira et al, 2014;Ternus et al, 2011). According to Rodier (1998) and Meneses-Campo et al (2019), the River Tambo have high mineralization, since the conductivity is higher than 1 000 µS/cm and these values rise progressively downriver, such as on stations E9, E8, E7, and E6 in this study, located in the middle to low zone of the river.…”
Section: Discussionmentioning
confidence: 46%
“…All twelve stations in this study showed high conductivity values. Sediment ingress because of the lack of riverside vegetation at all stations could be an explanation for these high values (Reis-Oliveira et al, 2014;Ternus et al, 2011). According to Rodier (1998) and Meneses-Campo et al (2019), the River Tambo have high mineralization, since the conductivity is higher than 1 000 µS/cm and these values rise progressively downriver, such as on stations E9, E8, E7, and E6 in this study, located in the middle to low zone of the river.…”
Section: Discussionmentioning
confidence: 46%
“…The problems caused by urbanization on stream ecosystems are accentuated in developing regions located in the tropics by problems related to culture, infrastructure and governmental actions (Agostinho et al 2005, Yule et al 2015. Unfortunately, little attention has been given to the ecological effects of urbanization on tropical rivers and streams (Yule et al 2015); also, few studies had been carried out in Brazilian urban streams, whether analyzing only the water quality (Cunha et al 2011, Oliveira et al 2014 or the structure of the benthic fauna (Cortezzi et al 2009, Souto et al 2011. More studies of urban stream ecology are vital for a better understanding of the processes involved and for implementation of better management actions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their better water quality conditions, the volumes (tributary water flow) are probably insufficient to cause a significant positive effect on the Tietê River. However, this is not a reason to neglect the potential contribution of the small and middle-size tributaries widely distributed along the Tietê River basin [46,47]. This process is especially important for observation in the near future, due to the present trend of sanitation measures implementation (sewage treatments plants) all over São Paulo State, after decades without effective actions.…”
Section: Environmental Conditionsmentioning
confidence: 99%